Lessons from Behavioral Economics to Improve Treatment Adherence in Parenting Programs: An Application to SMS - Nicolas Ajzenman; Florencia López Bóo (Institute of Labor Economics (IZA), 2019)
A growing literature shows how insights from behavioral economics can be successfully adopted in simple interventions through SMS or other types of low-cost communications. In this short, note we provide concrete basic guidelines to design behaviorally informed messages, based on theory and our own experience. We provide examples applied to parenting interventions.
Keywords: D9; D90; D91; I15; I38; J38; 330; behavioral interventions; parenting; child development; poverty